Bacterial and fungal microflore in fruits and vegetables - Musa, Mexhit; Hajdini, Sabri (Technium BioChemMed, 2022)
The aim of our research was the determination of the presence and density of bacteria and musk yeast in fruits and vegetables. We also have seen the reason to conclude about numerical and qualitative reports of fruits and vegetables which were examinate with heterotrophic bacteria, kaliformet totale and musk of yeasts. We had the curiosity to do the research of these data and also the comparison with other investigations in order to give a modest contribution on the density of investigated microflora in unit of measure for gram. of fruits and vegetables. Some fruits and vegetables have served as a material for the investigation. The materials have been collected in the green market, and in some markets of Mitrovica. The research methods have been methods with membrane filters. This method is the indirect method because of the results that were obtained, and they are also evidenced after the planting and incubation of the samples.